First measurements of aluminum erosion by neutral particles on EAST tokamak. (March 2021) - Mu, L.; Ding, R.; Liu, N.X.; Xie, H.; Gao, B.F.; Chen, J.L.
Highlights: Material erosion rates by neutral particles in EAST tokamak have been firstly measured. Higher plasma density can lead to higher material erosion rates. Theoretical analysis on material erosion rates by neutral particles is consistent with the measurements. Abstract: To evaluate the erosion effects of neutral particles on the first wall materials during tokamak operation, aluminum (Al) coated samples were exposed to a sequence of plasma discharges in 2018 and 2019 EAST campaigns. In order to avoid the incidence of charged particles, the samples were installed in a molybdenum (Mo) cylindrical sleeve and positioned far from the main plasma. The erosion thicknesses of Al layer were measured by Rutherford Backscattering Spectrometry (RBS) before and after the plasma exposure. The average net erosion rates of the samples in the two campaigns are around 1.18 × 10 13 atoms cm −2 s −1 and 4.64 × 10 13 atoms cm −2 s −1, respectively. The different erosion rate may mainly result from different plasma density and heating power. The theoretical calculated erosion rates using the neutral distribution under different density conditions are in fair agreement with the experimental results.